An Optimum Design of Cam Mechanisms with Roller Follower for Combined Effect of Impact and High Contact Loads - Al-Shamma, Fathi; Mustafa, Faiz F.; Saliman, Sahar M. (Al-Khwarizmi Engineering Journal, 2010)
The problem in the design of a cam is the analyzing of the mechanisms and dynamic forces that effect on the family of parametric polynomials for describing the motion curve. In present method, two ways have been taken for optimization of the cam size, first the high dynamic loading (such that impact and elastic stress waves propagation) from marine machine tool which translate by the roller follower to the cam surface and varies with time causes large contact loads and second it must include the factors of kinematics features including the acceleration, velocity, boundary condition and the unsymmetrical curvature of the cam profile for the motion curve.     In the theoretical solution the unidirectional impact stress waves with the Mushkelishvilis inverse of the singular integral equation for contact stress have been used for analytical solution and a numerical solution have bean solved using F.E.M (ANSYS 10) for stress analysis in a cam surface at condition of rise-dwell-return (R-D-R) motion of the follower, also to compare the analytical and numerical results that have been used different pressure angles in the rise and return of the motion curves in unsymmetrical cam profile for optimum design.